Patriarchal Propaganda on Archipelagic Folklores - Sufa, Amy Fayla (Universitas Sanata Dharma, 2023)
A folklore is a patriarchal propaganda, by carrying out stories that indoctrinate how mankind should behave, or how men and women have their role in society. This study aims to discover the patriarchal construct in archipelagic folklore and how archipelagic folklore gave rise to propaganda to the current patriarchal system. This study used a qualitative descriptive method using a mimetic and objective approach. The process of collecting data is through library study including sources taken from texts in the book